If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (n + 6)(n + -9) = 26 Reorder the terms: (6 + n)(n + -9) = 26 Reorder the terms: (6 + n)(-9 + n) = 26 Multiply (6 + n) * (-9 + n) (6(-9 + n) + n(-9 + n)) = 26 ((-9 * 6 + n * 6) + n(-9 + n)) = 26 ((-54 + 6n) + n(-9 + n)) = 26 (-54 + 6n + (-9 * n + n * n)) = 26 (-54 + 6n + (-9n + n2)) = 26 Combine like terms: 6n + -9n = -3n (-54 + -3n + n2) = 26 Solving -54 + -3n + n2 = 26 Solving for variable 'n'. Reorder the terms: -54 + -26 + -3n + n2 = 26 + -26 Combine like terms: -54 + -26 = -80 -80 + -3n + n2 = 26 + -26 Combine like terms: 26 + -26 = 0 -80 + -3n + n2 = 0 Begin completing the square. Move the constant term to the right: Add '80' to each side of the equation. -80 + -3n + 80 + n2 = 0 + 80 Reorder the terms: -80 + 80 + -3n + n2 = 0 + 80 Combine like terms: -80 + 80 = 0 0 + -3n + n2 = 0 + 80 -3n + n2 = 0 + 80 Combine like terms: 0 + 80 = 80 -3n + n2 = 80 The n term is -3n. Take half its coefficient (-1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. -3n + 2.25 + n2 = 80 + 2.25 Reorder the terms: 2.25 + -3n + n2 = 80 + 2.25 Combine like terms: 80 + 2.25 = 82.25 2.25 + -3n + n2 = 82.25 Factor a perfect square on the left side: (n + -1.5)(n + -1.5) = 82.25 Calculate the square root of the right side: 9.069178574 Break this problem into two subproblems by setting (n + -1.5) equal to 9.069178574 and -9.069178574.Subproblem 1
n + -1.5 = 9.069178574 Simplifying n + -1.5 = 9.069178574 Reorder the terms: -1.5 + n = 9.069178574 Solving -1.5 + n = 9.069178574 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + n = 9.069178574 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + n = 9.069178574 + 1.5 n = 9.069178574 + 1.5 Combine like terms: 9.069178574 + 1.5 = 10.569178574 n = 10.569178574 Simplifying n = 10.569178574Subproblem 2
n + -1.5 = -9.069178574 Simplifying n + -1.5 = -9.069178574 Reorder the terms: -1.5 + n = -9.069178574 Solving -1.5 + n = -9.069178574 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + n = -9.069178574 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + n = -9.069178574 + 1.5 n = -9.069178574 + 1.5 Combine like terms: -9.069178574 + 1.5 = -7.569178574 n = -7.569178574 Simplifying n = -7.569178574Solution
The solution to the problem is based on the solutions from the subproblems. n = {10.569178574, -7.569178574}
| 6(3x-5)+2(3x-5)-8(3x-5)= | | 3x+0=-15 | | 1x+36+64=80 | | 2x^2(4x^3-3x^2+6x)= | | 7+5p-4=9p+21-7p | | 1-q/Q=Q-q/Q | | x+0=8 | | 63x-1+24=31 | | 31/3+11/2 | | 2/3y+10=y/3+36/5 | | 5p+3/2=9 | | 7.2x+6.5=15.5 | | -2a^3+5a^2-a=2 | | 8x+2+44=110 | | 3x^2-28x+20=0 | | (x)+(1/3)(x)=60 | | -2p-4=-9 | | 137+16.5(x)=465 | | 137+16.5(x)=399 | | 9/3+2=5 | | 2x(x+6y+4z)= | | 6p+19p=150 | | 3(-3/4) | | x+3/2=14 | | 3x+1/x=4 | | 9(x-4)-x(x+3)+8(x^2+9)= | | 4x^2-x^3-3x=0 | | 12-4t=16 | | (2x+2)-(3x+11)= | | 7.4x+10=37 | | (x-1)(x-1)(x-1)= | | 5+x+(8x+9)= |